Food surplus as an alternative for the elaboration of new substrates for the cultivation of pleurotus ostreatus (Basidiomycota, Fungi) - Martins, Olívia Gomes [UNESP]; Abilio, Dalvan Pereira; Siqueira, Otávio Augusto Pessotto Alves [UNESP]; Ronchesel, Murilo; De Andrade, Meire Cristina Nogueira [UNESP] (Centro Universitario de Maringa, 2018)
The edible mushroom Pleurotus ostreatus, commonly known as shimeji or hiratake, secretes specialized enzymes that degrade materials rich in lignin and cellulose. It transforms these compounds into a nutrition source for its development. Different organic wastes are employed for the cultivation of P. ostreatus, such as rice and bean straw, elephant grass and others. Few studies exist on the use of food surplus for the culture of mushrooms and its use may become an effective and sustainable production manner, with lower costs and environmental impact when compared to the extraction of usually employed material such as sugarcane bagasse, straw and grasses. The viability of a compost based on food surplus at different proportions (T1=0%, T2=5%, T3=10%, T4=15%, T5=20%) is investigated for the culture of P. ostreatus. Evaluation criteria comprise the chemical traits of substrates, loss of organic material and biological efficiency. Treatment 1 had an average production of 333 g per package; Treatment 2 averaged 274 g; Treatment 3 averaged 217 g; Treatment 4 averaged 128 g; Treatment 5 averaged 113 g. Analysis of substrates indicated an increasing relationship between carbon and nitrogen and increase in the proportion of food surplus composts. Results showed a decrease in the productivity of each treatment and thus non-efficiency for production.
SOBRA DE ALIMENTOS COMO ALTERNATIVA PARA A FORMULAÇÃO DE NOVOS SUBSTRATOS PARA O CULTIVO DE Pleurotus ostreatus (BASIDIOMYCOTA, FUNGI)
Keywords: Edible mushrooms; Productivity; Use; Wastes